2020
DOI: 10.1021/acs.est.0c04641
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Microplastics on Nematodes in the Soil Environment: Tracking the Extractable Additives Using an Ecotoxicological Approach

Abstract: With an increasing interest in the effects of microplastic in the soil environment, there is a need to thoroughly evaluate potential adverse effects of these particles as a function of their characteristics (size, shape, and composition). In addition, extractable chemical additives from microplastic have been identified as an important toxicity pathway in the aquatic environment. However, we currently know little about effects of such additives in the soil environment. In this study on nematodes (Caenorhabditi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 147 publications
(69 citation statements)
references
References 89 publications
0
50
3
Order By: Relevance
“…Our results indicated that microplastic foams and fragments increased soil pH, which can be due to the increase in soil aeration and porosity when these microplastics were added into the soil (de Souza Machado et al, 2019;Lozano et al, 2021a). This along with the leaching of microplastic chemical compounds into the soil (Kim et al, 2020;Waldman and Rillig 2020), may alter soil biota with consequences for soil pH. Likewise, although slightly, microplastic films increased soil pH.…”
Section: Microplastics Increased Soil Phmentioning
confidence: 66%
“…Our results indicated that microplastic foams and fragments increased soil pH, which can be due to the increase in soil aeration and porosity when these microplastics were added into the soil (de Souza Machado et al, 2019;Lozano et al, 2021a). This along with the leaching of microplastic chemical compounds into the soil (Kim et al, 2020;Waldman and Rillig 2020), may alter soil biota with consequences for soil pH. Likewise, although slightly, microplastic films increased soil pH.…”
Section: Microplastics Increased Soil Phmentioning
confidence: 66%
“…MPs have potentially pervasive influences on terrestrial ecosystems, as exemplified here for the processes related to soil carbon storage. Examining these effects in detail will be an immense challenge, because MP particles come in a dizzying diversity of types [ 47 ] (including size, shape [ 48 ], aging-related modification [ 49 ], and nature of additives [ 50 , 51 ]) that very likely differ quite drastically in their effects. It is not clear how this need to account for the diversity of MP types can be reconciled with the logistic demands on ecosystem-level experimentation, such as in mesocosm or field experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in pore space may also lead to their habitat loss. Likewise, as microplastic fibres may potentially release harmful contaminants into the soil in the form of additives (Kim et al., 2020) or organic pollutants associated with fibre manufacturing (Hermabessiere et al., 2017), specific microorganisms could have been affected by these new environmental conditions (Rillig, de Souza Machado, et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Microplastic effects on ecosystem functions and multifunctionality can be related with their shape (Lozano, Lehnert, et al., 2021; Rillig, Ryo, Lehmann, et al., 2019) and very likely with the leaching of additives to the soil matrix. Indeed, recent research showed that microplastic fibres of polyacrylicnitrile may cause toxicity in the soil inducing negative effects on soil biota due to their extractable additives (Kim et al., 2020). Polyester fibres contain different water soluble hazardous additives (Table S1), which can potentially be released into the soil, affecting soil biota communities and therefore ecosystem functionality.…”
Section: Discussionmentioning
confidence: 99%